2010
DOI: 10.1667/rr1775.1
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of γ-H2AX Foci in Human Lymphocytes: A Method for Biological Dosimetry after Ionizing Radiation Exposure

Abstract: Recent studies have suggested that visualization of gamma-H2AX nuclear foci can be used to estimate exposure to very low doses of ionizing radiation. Although this approach is widely used for various purposes, its suitability for individual human biodosimetry has not yet been assessed. We therefore conducted such an assessment with the help of available software for observing and automatically scoring gamma-H2AX foci. The presence of gamma-H2AX foci was evaluated in human peripheral blood lymphocytes exposed e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
107
3
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 128 publications
(129 citation statements)
references
References 20 publications
18
107
3
1
Order By: Relevance
“…Therefore, efforts have been made to improve this method, based on microscopy techniques such as imaging modalities in cell culture and in tissues,162 and computer‐assisted approaches 163. The computational approaches are supported by image analysis software such as NIH Image and its Windows counterpart ScionImage, ImageJ, HistoLab, AutoQuantX, or Image Pro, among others, which rely on different computational algorithms for foci identification or the calculation of quantitative foci parameters 164, 165, 166. High content imaging systems are also capable of γH2AX quantitation.…”
Section: The γH2ax Assaymentioning
confidence: 99%
“…Therefore, efforts have been made to improve this method, based on microscopy techniques such as imaging modalities in cell culture and in tissues,162 and computer‐assisted approaches 163. The computational approaches are supported by image analysis software such as NIH Image and its Windows counterpart ScionImage, ImageJ, HistoLab, AutoQuantX, or Image Pro, among others, which rely on different computational algorithms for foci identification or the calculation of quantitative foci parameters 164, 165, 166. High content imaging systems are also capable of γH2AX quantitation.…”
Section: The γH2ax Assaymentioning
confidence: 99%
“…Two or three laboratories received samples from the same donor. Based on previous experience using the five donors and on published studies (Roch-Lef evre et al 2010;Chua et al 2011), any variability between the donors would be expected to make only a small contribution to overall uncertainties.…”
Section: Blood Sampling Irradiation and Shipmentmentioning
confidence: 99%
“…The gamma-H2AX foci assay is a sensitive surrogate marker of radiation induced DNA double strand breaks (Ivashkevich et al 2012;Rothkamm et al 2015) and may be a useful early biodosimetry tool from hours to about three days post-exposure (Roch-Lef evre et al 2010;Mandina et al 2011). Several studies have shown that rapid processing time of the gamma-H2AX assay can produce dose estimates within a few hours of receiving a blood sample (Rothkamm et al 2013a;Ainsbury et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Radioinduced DSB in DNA can be localized within the cell nuclei by a fluorescence labeling of γ-H2AX around the damages [1]. Nevertheless, DSB are also produced during the cell cycle, mainly during the cell duplication.…”
Section: The Experimental γ-H2ax Foci Distribution Acquisitionmentioning
confidence: 99%
“…The topological and quantitative analysis of these damages is now possible using immunofluorescence techniques [1]. Indeed, when a DSB occurs, many molecules of histone H2AX become phosphorilated (γ-H2AX) along megabase chromatin domains adjacent to the break as an early step of the DSB signaling and repair.…”
Section: Introductionmentioning
confidence: 99%